Study of the martensitic transition in Ni-Mn-Sn-Ti ferromagnetic shape memory alloys - Bonifacich, Federico Guillermo (2018)
In the present work, mechanical spectroscopy measurements as a function of temperature and strain have been performed in (at.%) Ni50Mn37Sn13-xTix (x=0, 0.5 and 2) ferromagnetic shape memory alloys in order both to study martensitic transition phenomenon and also to determine its temperature of appearance. For mechanical spectroscopy measurements, a five elements piezoelectric device recently developed has been used. In addition, other characterization techniques as, differential thermal analysis and superconducting quantum interference magnetic spectroscopy, were also used. Besides, relaxation processes near the martensitic transition temperature have been also observed.